Environmental Decision-Making and Community Involvement: Lessons From Ōwairaka - Wilson, Andrew (Auckland University of Technology, 2023)
This thesis is concerned with the meanings around stakeholder engagement expressed within an alignment of local community and Indigenous actors contesting environmental decision-making by Auckland Tāmaki Makaurau co-governance entity Tūpuna Maunga Authority (TMA). It focuses on the breakdown of collective goodwill when shared vision around the renaturing strategy for one of the city’s iconic maunga, Ōwairaka, is revealed at the implemetation level to involve the single-operation removal of all her existing exotic trees. Furthermore, it integrates the role of the media in shaping understandings of the protagonists’ perspectives and actions in the ensuing dispute and of the Treaty of Waitangi collective redress context within which the issue was situated. The case reveals escalating tensions that can arise when local community members, tangata whenua and mana whenua actors anticipate a significant loss of value, in historical, ancestral, spiritual and environmental dimensions from a co-governance entity’s decision-making around management of a natural resource. For the TMA, its decision-making around implementing the native restoration plans for Ōwairaka was deemed to be founded on value- creation in these dimensions for the wider public as well the entity’s purpose of enabling the exercise of mana whenua and kaitiakitanga for its iwi and hapū. For the contesting voices, environmental restoration of the maunga precluded removing non-pest exotic trees believed to have mauri and to support important existing natural ecosystems. For tangata whenua and mana whenua amongst these voices, their identities interwoven with kaitiaki obligations to the maunga, this meant allowing the exotics to transition through the natural cycles of te taiao, fulfilling their role as canopy, nursery for seedlings and habitat for fauna - an approach not seen as mutually exclusive of the renaturing objectives of the TMA. The findings reveal how these contesting voices expressed the legitimacy of their claims, incorporating meanings with respect to their connection to the maunga, to the protection of her environment and to their relationships with and expectations of engagement from the TMA. They uncover a racist underbelly in Aotearoa New Zealand that served to cloud the issues in dispute. They also reveal a layer of complexity that arose when one of the contesting voices, Ngāti Whātua Ōrākei, hapū represented on the TMA, achieved High Court acknowledgement of its mana whenua status based on ahi kā with respect to Ōwairaka, bringing with this an expectation of higher-level consultation within the Authority. Moreover, the case brings to light tensions around differing tribal approaches to kaitiakitanga and tikanga around engagement with local communities and the environmental management of co-governed resources. The case opens up for consideration the prerogative of the TMA to persist in its stance that, in having its renaturing strategy for the maunga approved in its public submissions stage, this permitted operational decisions to be made without further public notification or local community consultation. It provides an alternative perspective of a more flexible stakeholder engagement approach based around anticipating and/or responding to claims of loss of value by community stakeholders that arise as a result of decisions and seeking compromise if necessary.